2020
DOI: 10.1002/alr.22517
|View full text |Cite
|
Sign up to set email alerts
|

Use of mucosal eosinophil count as a guide in the management of chronic rhinosinusitis

Abstract: Background: Chronic rhinosinusitis (CRS) is a local inflammatory process driven by eosinophils. Mucosal eosinophil count (MEC) has previously been demonstrated to be a reliable indicator of disease severity. We aim to evaluate use of MEC in guiding medical management of CRS a er functional endoscopic sinus surgery (FESS). Methods:We retrospectively reviewed patients with CRS who underwent FESS from 2004 to 2017. Tissue MEC per high-power field (HPF) was determined by pathologic examination. MECs were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…According to the prior reports, eosinophils have been implicated in a variety of biological functions ( 109 ), including mediating inflammation or inducing immunity. Moreover, studies have found that eosinophilia is positively correlated with the severity of CRS, thus indicating that more the number of eosinophils, greater is the severity of the disease ( 110 ). This is in addition to the pro-inflammatory role of eosinophils in releasing IL-4, IL-5, and IL-13 cytokines.…”
Section: Important Immune and Effector Cells Involved In Crs Remodeli...mentioning
confidence: 99%
“…According to the prior reports, eosinophils have been implicated in a variety of biological functions ( 109 ), including mediating inflammation or inducing immunity. Moreover, studies have found that eosinophilia is positively correlated with the severity of CRS, thus indicating that more the number of eosinophils, greater is the severity of the disease ( 110 ). This is in addition to the pro-inflammatory role of eosinophils in releasing IL-4, IL-5, and IL-13 cytokines.…”
Section: Important Immune and Effector Cells Involved In Crs Remodeli...mentioning
confidence: 99%
“…2,3 Some have even proposed that eosinophilia could serve as a guide for patient management. [4][5][6][7] Previous studies have evaluated associations of tissue eosinophil density with disease severity, olfactory function, and patient-reported quality-of-life (QoL). [8][9][10] Evaluations of neutrophilia have demonstrated some variations in disease severity, but the association between mucosal neutrophilia and clinical features of CRS has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory sinonasal disease, which involves various molecular and cellular pathways 1 . Although CRSwNP is a heterogeneous disorder characterized by distinct combinations of T‐cell and granulocyte responses, the eosinophilic feature is recognized as a pivotal trait of the disease and eosinophils are useful biomarkers in clinical practice for monitoring disease severity and control in CRSwNP patients 2–4 . Both mucosal and blood eosinophilia are associated with disease severity and postsurgical recurrence in CRSwNP patients 5–13 …”
mentioning
confidence: 99%